Blood-nerve barrier disruption and coagulation system activation induced by mechanical compression injury participate in the peripheral sensitization of trigeminal neuralgia - Zhou, Lu-Xi; Lin, Shao-Wei; Qiu, Rong-Hui; Lin, Ling; Guo, Yue-Feng; Luo, Dao-Shu; Li, Yun-Qing; Wang, Feng (Frontiers in Molecular Neuroscience, 2022)
Introduction The aim of this study was to investigate the effect and possible mechanisms of the blood-nerve barrier (BNB) and the coagulation-anticoagulation system in modulating the mechanical allodynia in a trigeminal neuralgia (TN) rat model induced by chronic compression of the trigeminal root entry zone (TREZ). Methods Von Frey filaments were applied to determine the orofacial mechanical allodynia threshold. The BNB permeability was evaluated by Evans blue extravasation test. Immunohistochemical staining and laser confocal microscopy were used to measure the length of the depletion zones of the nodes of Ranvier in the TREZ, the diameter of nerve fibers and the length of the nodal gap. The transcriptional levels of prothrombin and endogenous thrombin inhibitor protease nexin-1 (PN-1) in the TREZ of TN rats were assessed by RT-qPCR. A Western blotting assay was performed to detect the expression of paranodal proteins neurofascin-155 (NF155) and neurofascin-125 (NF125) in the TREZ. The spatiotemporal expression pattern of thrombin activated receptor (i.e. protease activated receptor 1, PAR1) in TREZ were defined by immunostaining and immunoblotting assays. PAR1 receptor inhibitors SCH79797 were administrated to TN rats to analyze the effect of thrombin-PAR1 on orofacial hyperalgesia. Results A compression injury of a rat’s TREZ successfully induced TN-like behavior and was accompanied by the destruction of the permeability of the BNB and the promotion of prothrombin and thrombin inhibitor protease nexin-1 (PN-1) expression. The expression of the paranodal proteins neurofascin-155 (NF155) and neurofascin-125 (NF125) was increased, while the nodal gap length of the nodes of Ranvier was widened and the length of node-depleted zones was shortened. Moreover, the expression of PAR1 within the TREZ was upregulated at an early stage of TN, and administration of the PAR1 antagonist SCH79797 effectively ameliorated orofacial mechanical allodynia. Conclusion A compression injury of the TREZ increased the permeability of the BNB and induced disturbances in the local coagulation-anticoagulation system, concomitant with the structural changes in the nodes of Ranvier, thrombin-PAR1 may play a critical role in modulating orofacial mechanical hyperalgesia in a TN rat model.